What Constitutes a Scientific Interpretation of Religion? - Faris, Ellsworth (The journal of religion, 1926)
The scientific interpretation of religion must include an understanding of its origin, a differentiation from closely related activities, and a statement of its function. The origin is still hypothetical, but clearly depends upon the efforts of groups to realize their deferred desires. Religion is distinguished from science, for science is instrumental, and from theology, which is a rationalized defense. The problem of the function of religion is the problem of the place of ideals in our social life and the place of the group efforts to communicate these ideals.